The fractional amplitude of low-frequency fluctuations signals related to amyloid uptake in high-risk populations—A pilot fMRI study - Bao, Yi-Wen; Shea, Yat-Fung; Chiu, Patrick Ka-Chun; Kwan, Joseph S. K.; Chan, Felix Hon-Wai; Chow, Wing-Sun; Chan, Koon-Ho; Mak, Henry Ka-Fung (Frontiers in Aging Neuroscience, 2022)
Background T2DM and SCD patients have a higher risk to develop AD. Rs-fMRI is able to document neurological involvement in two groups from the aspect of brain dysfunction. Amyloid-β observed to accumulate many decades before the onset of clinical symptoms may already have been associated with brain function in high-risk populations. This study aims to compare the patterns of fALFF maps between cognitively normal high-risk groups (SCD and T2DM) and healthy elderly and evaluate the association between regional amyloid deposition and local fALFF signals in certain cortical regions. Materials and Methods A total of 18 T2DM, 11 SCD and 18 healthy elderlies was included in this study. The differences of the fALFF maps were compared between HC and high-risk groups. Regional amyloid deposition and local fALFF signals were obtained and further correlated in two high-risk groups. Results Compared to HC, the altered fALFF signals of regions shown in SCD such as the left posterior cerebellum and left putamen. The T2DM group illustrated altered neural activity in the superior temporal gyrus, supplementary motor area and precentral gyrus. The correlation between fALFF signals and amyloid deposition was negative in the left anterior cingulate cortex for both groups. In the T2DM group, a positive correlation showed in the right occipital lobe and left mesial temporal lobe. Conclusion The altered fALFF signals were demonstrated in high-risk groups compared to HC. Very early amyloid deposition in SCD and T2DM groups was observed to affect the neural activity mainly involved in the default mode network.